Performance of newly released ’Kufri Chipsona 3’ Indian potato vareity during - PANDEY, S K; SINGH, S V; KUMAR, DINESH; MARWAHA, R S; MANIWAL, P; KUMAR, PARVEEN (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2003-04 and 2004-05 to evaluate the newly released ‘Kufri Chipsona 3’ cultivar of potato (Solanum tubersoum L.) for its yield and chipping quality in different seasons in west-central plains. ‘Kufri Chipsona 3’ was found superior to existing indigenous processing cultivars ‘Kufri Chipsona 1’, ‘Kufri Chipsona 2’ and exotic cultivar ’Atlantic’ in terms of total and processing grade tuber yield when harvested at 75 days in early autumn season, at 110 days in main autumn season and 100 days in late autumn season. Best chipping quality of its tubers was obtained at 75 days in early autumn season and at 110 days in main autumn season while the late autumn crop was not suitable for chipping. However, the potatoes from late autumn crop had high dry matter content and could be suitable for making dehydrated products